Beyond-school mathematical problem solving: a case of students-with-media - Jacinto, Hélia (2018)
This paper addresses mathematical problem solving activity within the context of a web-based beyond-school competition – SUB14. Using a qualitative approach, we aim at finding evidences of the contestants’ mathematical competence and technological fluency by analysing four solutions to a particular geometry problem from participants who decided to use GeoGebra. Even though they all make use of the same tool, their approaches to the problem differ in terms of the mathematical and technological fluency they show. We interpret their different ways of dealing with the tool and with mathematical knowledge as instances of students-with-media in problem solving.